Can low doses of glyphosate stimulate common bean growth? - Bortolheiro, Fernanda Pacheco de Almeida Prado [UNESP]; Brunelli-Nascentes, Marcela Cristina [UNESP]; Boaro, Carmen Sílvia Fernandes [UNESP]; Silva, Marcelo de Almeida [UNESP] (Taylor & Francis, 2021)
Plant growth can be stimulated by low doses of glyphosate. The objective of this work was to evaluate the effect of low doses of glyphosate and sowing season on the growth of the early cycle common bean. Two experiments were conducted in the field, the first in the winter and the second in the wet season, with the early cycle common bean cultivar IAC Imperador. The experimental design was a randomized complete block design, consisting of low doses of glyphosate applied on phenological stage V4, with four replications. Environmental conditions, such as air temperature, interfered in the early cycle common bean response to low doses of glyphosate. In the winter season, a dose of 36 g a.e. ha−1 promoted growth in the common bean, and a dose of 7.2 g a.e. ha−1 improved the harvest index. In the wet season, there was no growth stimulus, and the harvest index increased with a dose of 36 g a.e. ha−1. The harvest index was the only characteristic improved in both seasons, but with different doses. Our study indicates that growth characteristics of early cycle common bean are stimulated by low doses of glyphosate, but this response is dependent on the growing environment.
Keywords: early cycle cultivar; hormesis; morphology; Phaseolus vulgaris L; quantitative growth analysis